2015
DOI: 10.1080/02103702.2014.996403
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative solving of information problems and group learning outcomes in secondary education / Resolución colaborativa de problemas informacionales y resultados de aprendizaje grupal en la educación secundaria

Abstract: This research focuses on the study of the processes of collaborative solving of information problems and their impact on group learning outcomes. Forty-nine pairs of students solved three learning tasks with learning goals of increasing complexity: information selection, information interpretation, and interrelating concepts. We analysed two types of data: group work processes and group learning outcomes. The group work processes were assessed using eight dimensions, and group learning outcomes were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…Following previous studies (Badia & Becerril, 2015;De Vries, Van der Meij & Lazonder, 2008;Morris et al, 2010;Pifarré, 2009;Pifarré, Cobos, & Argelagós, 2014;Stadtler & Bromme, 2008;Walraven et al, 2010, Wopereis, Brand-Gruwel, & Vermetten, 2008, the instructional process might be scaffolded by means of questions, worksheets, scripts, and prompts (Stadler & Brome, 2008). For instance, scaffolds could be designed as it follows: (a) driving questions in order to encourage the activation of students' prior knowledge; (b) prompts to perform a specific IPS skill, i.e.,…”
Section: Conclusion and Educational Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following previous studies (Badia & Becerril, 2015;De Vries, Van der Meij & Lazonder, 2008;Morris et al, 2010;Pifarré, 2009;Pifarré, Cobos, & Argelagós, 2014;Stadtler & Bromme, 2008;Walraven et al, 2010, Wopereis, Brand-Gruwel, & Vermetten, 2008, the instructional process might be scaffolded by means of questions, worksheets, scripts, and prompts (Stadler & Brome, 2008). For instance, scaffolds could be designed as it follows: (a) driving questions in order to encourage the activation of students' prior knowledge; (b) prompts to perform a specific IPS skill, i.e.,…”
Section: Conclusion and Educational Implicationsmentioning
confidence: 99%
“…However, it is widely accepted that the complex cognitive activities involved in gathering and processing information from the Web are not instinctively acquired (Wood, 2009). Previous research has shown that students have difficulties in mastering these skills (Badia & Becerril, 2015;Bannert & Reimann, 2011;Walraven, Brand-Gruwel, & Boshuizen, 2008;Wood, 2009) and it is claimed that more research in studying the nature of these challenges is needed. This new research should fuel on well-designed and well-embedded scaffolds given to students in order to promote better students' digital skills development which will allow them to reach a stronger educational attainment (e.g., Raes, Schellens, De Wever, & Vanderhoven, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Following previous studies (Badía & Becerril, 2015;Pifarré, 2009;Pifarré, Cobos, & Argelagós, 2014;Walraven et al, 2010;Wopereis et al, 2008), the instructional process might be scaffolded by means of questions, worksheets, scripts, and prompts (Stadler & Brome, 2008). For instance, scaffolds could be designed as it follows: (a) driving questions in order to encourage the activation of students' prior knowledge; (b) prompts to perform a specific IPS skill, i.e., "write down the specific information you will need to solve this problem" (skill defining the problem); (c) pop-up messages to guide a search; and (d) worksheets to promote reflection about search terms or selection of the results (skill searching information).…”
Section: Instructional Applicationsmentioning
confidence: 99%
“…Since the Internet is an extensive source of information, IPS skills and regulation activities are necessary in order to be successful in web-based learning (Brand-Gruwel, Wopereis, & Vermetten, 2005;Brand-Gruwel, Wopereis, & Walraven, 2009). Nevertheless, contemporary cognitive and educational research has shown that most students have difficulty in performing IPS skills and regulating their learning spontaneously (Badía & Becerril, 2015;Bannert & Reimann, 2011;Lazonder & Rouet, 2008;Walraven, Brand-Gruwel, & Boshuizen, 2008;Wood, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When an information problem is resolved within the framework of peer learning, the shared construction of knowledge must also be taken into consideration (Badia & Becerril, 2015). Sharing knowledge means that two or more members of a group have cognitive representations that are somewhat similar (Fischer, Bruhn, Gräsel, & Mandl, 2002).…”
mentioning
confidence: 99%